Design of fuel control system using fuzzy logic for a pre-designed radial gas turbine driving directly high-speed permanent magnet alternator. (1st October 2016) - Ebaid, Munzer S. Y.; Al-fahoum, Amjed
Abstract: Radial gas turbine of 50-kW power output coupled directly to a high-speed permanent magnet alternator could be a favourable option as an emergency power plant at areas suffering from severe disasters, such as earthquakes, floods and volcanoes. This study aims to use the results of the subtractive clustering algorithm and the least square estimation method to generate a fuzzy model of the pre-designed radial gas turbine system whereby the fuzzy model takes the fuel mass flow rate as an input, and gives the value of the gas turbine net work W net as an output. In addition, a suitable controller of the fuel mass flow rate is designed and analysed so that the speed of the gas turbine and the alternator is maintained at 42, 000 rpm. A proportional derivative fuzzy controller was built and tested. Results illustrate that the proposed controller achieves the desired performance and stability, and showed the effectiveness of the approach. Conclusions of this study will constitute a base for further studies that could be made to enhance the performance of the proposed emergency power plant system.